A Critical Study of Crusoe’s Mind and Character - M.Kh. Niyazova, PhD; N. M. Subxonova (Genius Journals, 2023)
This article deals with Daniel Defoe's Robinson Crusoe is considered as the most important precursor of the English Novel or even as the first English Novel. Literary critics have discussed the character of Robinson Crusoe from different literary perspectives. The purpose of this article is to examine Crusoe's attitude towards business, religion arid nonEuropeans in its historical context. These three elements of Crusoe's character are inseparably linked to each other and are therefore essential to an appreciation of Crusoe's mind and character.
Keywords: English novels; classification; mind and characters